Optimisation of DNA extraction from teeth submerged in sea water in False Bay, South Africa - Longden-Thurgood, Chandra (Department of Pathology, 2019)
Extracting forensically useable DNA from human remains recovered from an open marine environment is problematic, and in some cases, impossible. The reason is unclear given the lack of research on marine decomposition, DNA survival in seawater, and possible methods to optimise the DNA extraction workflow. Compounding this problem is the fact that South Africa experiences a high number of unidentified human bodies entering its mortuaries each year, and these individuals often remain unidentified. The aim of the study was to extract forensically useable DNA from pig (Sus scrofa) teeth submerged in-situ in an open marine environment, by a process of optimisation and implementation. Detailed environmental information was available for this study. A DNA extraction technique was developed and optimised on “fresh” control pig teeth (n = 13). The developed methods for decontamination, tooth sampling, and the optimised DNA extraction protocol were successfully performed on these, with forensically useable DNA obtained. However, this was not the case for the subsample of experimental pig teeth (n = 6) tested. Implementation of the developed method on a larger sample of experimental teeth (n = 28) was warranted to assess the recovery of nDNA and mtDNA. Amplification of nDNA by qPCR was successful in 60% (17/28) of samples for a 96 bp fragment, and in 46% (13/28) for 200 bp. By comparison, mtDNA showed a detection rate of 57% (16/28) for a 486 bp fragment via PCR amplification. In seven samples mtDNA was detected where nDNA was not, demonstrating improved survivability in seawater. Colder and more stable seawater temperatures is hypothesised to have preserved molecular elements. DNA hydrolysis and the possibility of DNAase activity from marine bacteria, may have contributed to poor DNA preservation in the other samples. Recovery of DNA from teeth submerged in an open marine environment is complex and requires further investigation in human samples to improve the identification process for individuals who have died at sea.